Psychometric properties of the Indonesian online version of fertility quality of life tool: a cross-sectional study - Damayanti, Fitri; Hakimi, Mohammad; Anwar, Mochamad; Puspandari, Diah Ayu (International Journal Of Community Medicine And Public Health, 2021)
Background: The clinical measurement of an infertile couple’s quality of life (QoL) should be considered as a standard assessment of their pretreatment condition to aid in medical and psychological consultation. The study aimed to test the psychometric properties of the Indonesian online version of the fertility quality-of-life (FertiQoL) questionnaire. Methods: This study applied cross-sectional methods among women/men over 18 years who have problems with infertility and have or have not undergone any medical treatment. PT. Integra Inovasi Indonesia helped develop the online FertiQoL questionnaire. This research applied R project version 3.6.3 to merge the data and conduct statistical analyses. Pearson correlation tests were used to ensure the validity. Cronbach’s alpha coefficient test was also used to measure the instrument’s quality and reliability. Results: There were 214 participants enrolled from all over Indonesia. The total scores for core FertiQoL and treatment FertiQoL were 64.72±13.87 and 62.93±12.50, respectively. The total FertiQoL mean was 64.14±12.33. The reliability of the FertiQoL version of the Indonesian language was relatively high (Cronbach α was 0.92, and the value for each domain was >0.70 (0.76-0.94). The validity results of the FertiQoL questionnaire also showed that all question items were considered valid (r>0.1341). Conclusions: The Indonesian version of FertiQoL is valid and reliable for assessment of the pre-treatment condition of infertile couples and the effects of treatment on QoL in infertile patients which can help in making more accurate diagnosis and providing diagnosis and treatment in infertility clinics.